(untitled) (Revista Argentina de Cirugía, 2021)
Atypical gastric resection has proved to be beneficial to treat submucosal tumors. The technique is more difficult when these tumors develop next to the gastroesophageal junction (GEJ). Intragastric resection combining endoscopic and laparoscopic approach was proposed to solve this limitation. There are no publications about this technique in our environment. A 42-year-old female patients with a 2-mm subepithelial tumor below the cardia evaluated by upper gastrointestinal (UGI) videoendoscopy and endoscopic ultrasound suggestive of a gastrointestinal stroma tumor (GIST) underwent resection using the combined laparo-endoscopic approach. Under laparoscopic guidance, balloon-tipped trocars were introduced in the abdominal cavity and then into the stomach using endoscopic view. The balloons were inflated to fix the gastirc wall to the abdominal wall. The lesion was resected using mechanical stapler. The combined approach is safe and efficient, and simple to perform for trained professionals, constituting a reproducible option in selected cases.